Optimizing Human Capital Investment: VARK Learning Styles to Reduce Student Educational Costs - Lisa Gresti Sella Damanik; Xenia Irene Sandy Landjang (AIBPM Publisher, 2025)
The rising cost of higher education is a growing concern, particularly in regions with limited resources such as Papua, Indonesia, where academic challenges and extended study durations increase financial burden. This study examines the influence of VARK (Visual, Auditory, Read/Write, Kinesthetic) learning style identification and learning environment optimization on student educational cost reduction, with academic performance as a mediating variable. The sample consisted of 180 management students at Universitas Cenderawasih, with 125 respondents selected using Slovin’s formula. Data were collected through structured questionnaires and analyzed using PLS-SEM (SmartPLS 3). The results indicate that learning style identification significantly improves academic performance (? = 0.421; p 0.001) and reduces educational costs (? = 0.255; p = 0.007). Learning environment optimization also positively affects academic performance (? = 0.413; p 0.001) and cost reduction (? = 0.234; p = 0.024). Academic performance strongly influences cost reduction (? = 0.380; p = 0.002) and mediates the effects of X1 ? Z (? = 0.160; p = 0.010) and X2 ? Z (? = 0.157; p = 0.006). The model demonstrates moderate explanatory power (R² = 0.539 for Academic Performance; R² = 0.569 for Student Educational Costs). The findings highlight the importance of personalized learning and optimized environments in reducing financial burden.